Impact of cone beam computed tomography on periapical assessment and treatment planning five to eleven years after surgical endodontic retreatment. (16th February 2018) - Kruse, C.; Spin‐Neto, R.; Wenzel, A.; Væth, M.; Kirkevang, L.‐L.
Abstract: Aim: To evaluate how additional information from Cone Beam CT (CBCT) impacts on periapical assessment and treatment planning based on clinical examination and periapical radiographs (PR) in cases followed up five to eleven years after surgical endodontic retreatment (SER). Methodology: Patients receiving SER during 2004–2010 were reinvited for follow‐up examination including clinical examination, PR, and CBCT. In total, 108 patients (119 teeth) were reinvited, 74 patients (83 teeth) accepted to participate. Three observers initially assessed PR according to the four‐scaled, increasing disease severity criteria by Rud et al . ( International Journal of Oral Surgery, 1, 1972 and 195) and Molven et al . ( International Journal of Oral and Maxillofacial Surgery, 16, 1987 and 432): 'Radiographic assessment A'. By including clinical information 'Treatment plan A' was made as follows: 1) no treatment, 2) further observation, 3) SER reoperation (SER‐R), or 4) extraction. Hereafter, the CBCT volume was assessed and the information incorporated for 'Radiographic assessment B' followed by 'Treatment plan B'. Agreement between radiographic assessments and between treatment plans was recorded and assessed statistically by Stuart–Maxwell test for marginal homogeneity. Results: Nine teeth had been extracted; thus, the final analysis included 74 teeth (66 patients). The radiographic assessment was changed as a result of the CBCT evaluation in 38 cases (51.4%), of which 35 (47.3%) were to a higher Rud & Molven score, P < 0.001. The treatment plan was changed for 18 teeth (24.3%). For 14 teeth (18.9%), the change was from no treatment or further observation to a more invasive treatment plan (SER‐R or extraction), P = 0.005. Conclusion: The use of CBCT for long‐term follow‐up after SER led to more cases diagnosed with persisting or recurrent apical periodontitis and hence often to the recommendation of a more invasive treatment modality.